2020
DOI: 10.2147/dmso.s228335
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum Ferritin Independently Predicts the Incidence of Chronic Kidney Disease in Patients with Type 2 Diabetes Mellitus</p>

Abstract: Aim: This study aimed to determine whether serum ferritin (SF) is an independent risk factor of the incidence of chronic kidney disease (CKD) and rapid renal function decline (RFD) in male Tibetan patients with type 2 diabetes mellitus (T2DM). Methods: We performed a retrospective cohort study that included 191 male Tibetan patients with T2DM without CKD. Patients were divided into three groups according to the level of SF. The following outcomes were measured: cumulative incidence of chronic kidney disease [i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Our findings may have important clinical implications as the identification of T2DM patients with NAFLD and mildly elevated plasma ferritin levels might identify a subset of individuals at higher risk of having fibrotic NAFLD. In addition, it should be noted that higher plasma ferritin levels are associated with an increased risk of adverse cardiovascular 18,36,37 and renal outcomes 38 . Therefore, the results of our study highlight the need to early assess and adequately treat all coexisting cardiometabolic risk factors in T2DM patients with NAFLD and elevated ferritin levels, as also supported by a recent international consensus on the definition and classification of metabolic hyperferritinemia 9 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our findings may have important clinical implications as the identification of T2DM patients with NAFLD and mildly elevated plasma ferritin levels might identify a subset of individuals at higher risk of having fibrotic NAFLD. In addition, it should be noted that higher plasma ferritin levels are associated with an increased risk of adverse cardiovascular 18,36,37 and renal outcomes 38 . Therefore, the results of our study highlight the need to early assess and adequately treat all coexisting cardiometabolic risk factors in T2DM patients with NAFLD and elevated ferritin levels, as also supported by a recent international consensus on the definition and classification of metabolic hyperferritinemia 9 .…”
Section: Discussionsupporting
confidence: 66%
“…In addition, it should be noted that higher plasma ferritin levels are associated with an increased risk of adverse cardiovascular 18,36,37 and renal outcomes. 38 Therefore, the results of our study highlight the need to early assess and adequately treat all coexisting cardiometabolic risk factors in T2DM patients with NAFLD and elevated ferritin levels, as also supported by a recent international consensus on the definition and classification of metabolic hyperferritinemia. 9 Currently, lifestyle intervention (achieving a 5% to 10% weight loss through increased physical activity and a hypocaloric diet with a Mediterranean-style dietary pattern) is the cornerstone of the treatment of NAFLD and may also improve cardiometabolic risk factors and reduce metabolic hyperferritinemia.…”
Section: Logistic Regression Analysis (Ysupporting
confidence: 69%
“…Hsu et al 30 showed that hyperferritinemia may be an independent risk factor of nephropathy in patients with T2DM. Wu et al 31 reported that serum ferritin independently predicts the incidence of chronic kidney disease in patients with T2DM. Our study showed that there was a positive correlation between hyperferritinemia and DR, regardless of sex.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found that TIBC, transferrin, haemoglobin and eGFR were negatively correlated with creatinine. Recently it has been reported that raised levels of serum ferritin may play a role in the pathogenesis leading to the development of CKD in T2DM [13]. Also, serum ferritin level has been found as a prognostic marker for predicting renal recovery in acute kidney injury [14].…”
Section: Discussionmentioning
confidence: 99%